First records of Brazilian three-banded armadillo (Tolypeutes tricinctus, Mammalia, Cingulata, Chlamyphoridae) predation by jaguar (Panthera onca, Mammalia, Carnivora, Felidae) - Magalhães, Rodolfo Assis; Sena, Liana Mara Mendes de; Rodrigues, Flávio Henrique Guimarães (Papéis Avulsos de Zoologia, 2021)
The jaguar Panthera onca and the Brazilian three-banded armadillo Tolypeutes tricinctus are two threatened mammals that coexist in the Caatinga dry forests and the Cerrado savannas of Brazil. Yet, to the best of our knowledge, interactions between these species have not been reported in the literature. Here, we present the first records of P. onca predation on T. tricinctus from two different areas in the Caatinga in northeastern Brazil. We showed that P. onca can pierce the hard carapace of T. tricinctus, which may be possible due to its distinctly strong bite and associated predation behavior. We argue that P. onca may be the most adapted non-human predator to feed on T. tricinctus, and that the smaller body sizes of P. onca individuals in the Caatinga may increase their likelihood to feed on smaller prey, including T. tricinctus. Thus, the originality of our records is probably more related to insufficient research in the areas where these species coexist than to the rarity of this interaction.